Project Governance, Project Performance, and the Mediating Role of Project Quality and Project Management Risk: An Agency Theory Perspective. Issue 4 (2nd October 2018) - Haq, Saif Ul; Liang, Changyong; Gu, Dongxiao; Du, Jia Tina; Zhao, Shuping
Abstract: Although project governance has garnered the attention of academicians, the area remains underdeveloped. This study measures the influence of project governance on project performance directly as well as through the mediation of project management risk and project quality and with moderation of project leadership. The survey yielded 354 responses from 132 Pakistani software firms, while SEM was applied using AMOS-21 for data analysis. This study finds that project governance has a significant positive influence on project performance directly and through mediation, whereas the moderation is insignificant. The findings will help not only Pakistan's software firms but also those in developing countries to improve their projects' performance through effective project governance.